2021
DOI: 10.3389/fendo.2021.727272
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Antioxidant Paradigm of Mesenchymal Stem Cell-Derived Exosome Therapy

Abstract: Mesenchymal stem cell-derived exosomes have been under investigation as potential treatments for a diverse range of diseases, and many animal and clinical trials have achieved encouraging results. However, it is well known that the biological activity of the exosomes is key to their therapeutic properties; however, till date, it has not been completely understood. Previous studies have provided different explanations of therapeutic mechanisms of the exosomes, including anti-inflammatory, immunomodulatory, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 139 publications
(189 reference statements)
0
24
0
Order By: Relevance
“…Although the above studies show that SEVs can serve as cargoes for miRNA delivery, lipoproteins have also been proven to deliver miRNAs. Actually, lipoproteins are inevitably mixed with SEVs [70], making further purification of SEVs become one of the major obstacles in current SEVs research. Table 3 lists the mechanistic role of some SEVs-delivered miRNAs in myocardial protection.…”
Section: Mechanisms Of Msc-sevs On Myocardial Protectionmentioning
confidence: 99%
“…Although the above studies show that SEVs can serve as cargoes for miRNA delivery, lipoproteins have also been proven to deliver miRNAs. Actually, lipoproteins are inevitably mixed with SEVs [70], making further purification of SEVs become one of the major obstacles in current SEVs research. Table 3 lists the mechanistic role of some SEVs-delivered miRNAs in myocardial protection.…”
Section: Mechanisms Of Msc-sevs On Myocardial Protectionmentioning
confidence: 99%
“…68,69,70,71 In addition, MSCs are amongst the largest cellular procedures of exosomes, which have amounts of cargoes, including 850 gene products and 150 miRNAs described, and play a vital role in the regulation of inflammation, metabolic disorders, and cell damages. [72][73][74] Accumulating evidence has demonstrated that MSC-derived exosomes are considered to be a potential option for the treatment of human disease, such as Alzheimer's disease (AD), osteoarthritis, and autoimmune disease. [75][76][77] Although MSC-derived exosomes show increasing potential for human disease, there is still a lack of evidence.…”
Section: Mesenchymal Stem Cell (Mscs)-derived Exosomesmentioning
confidence: 99%
“…It has been found that Exo can diminish cell death and apoptosis via engaging several mechanisms. For instance, MSCs Exo can prevent detrimental effects of oxidative stress in degenerating cells via the regulation of reactive oxygen production 25 . The production of several inflammatory cytokines such as interleukin‐1 (IL‐1) and IL‐6, tumor necrosis factor (TNF)‐α in during COVID‐19 can trigger the mitochondrial injury via the production of hydrogen peroxide and inducible nitric oxide synthase 26 .…”
Section: Therapeutic Effects Of Exo During Infection With Sars‐cov‐2mentioning
confidence: 99%
“…For instance, MSCs Exo can prevent detrimental effects of oxidative stress in degenerating cells via the regulation of reactive oxygen production. 25 The production of several inflammatory cytokines such as interleukin‐1 (IL‐1) and IL‐6, tumor necrosis factor (TNF)‐α in during COVID‐19 can trigger the mitochondrial injury via the production of hydrogen peroxide and inducible nitric oxide synthase. 26 Besides, nasal and pulmonary epithelium failed to produce and secret antiviral factors such as interferon at early stages after infection with SARS‐CoV‐2.…”
Section: Therapeutic Effects Of Exo During Infection With Sars‐cov‐2mentioning
confidence: 99%